[11C]-(R)-PK11195 positron emission tomography in patients with complex regional pain syndrome: A pilot study. Issue 1 (January 2017) - Jeon, So Yeon; Seo, Seongho; Lee, Jae Sung; Choi, Soo-Hee; Lee, Do-Hyeong; Jung, Ye-Ha; Song, Man-Kyu; Lee, Kyung-Jun; Kim, Yong Chul; Kwon, Hyun Woo; Im, Hyung-Jun; Lee, Dong Soo; et al.
Abstract : Abstract: Complex regional pain syndrome (CRPS) is characterized by severe and chronic pain, but the pathophysiology of this disease are not clearly understood. The primary aim of our case–control study was to explore neuroinflammation in patients with CRPS using positron emission tomography (PET), with an 18-kDa translocator protein specific radioligand [ 11 C]-( R )-PK11195. [ 11 C]-( R )-PK11195 PET scans were acquired for 11 patients with CRPS (30–55 years) and 12 control subjects (30–52 years). Parametric image of distribution volume ratio (DVR) for each participant was generated by applying a relative equilibrium-based graphical analysis. The DVR of [ 11 C]-( R )-PK11195 in the caudate nucleus ( t (21)  = −3.209, P  = 0.004), putamen ( t (21)  = −2.492, P  = 0.022), nucleus accumbens ( t (21)  = −2.218, P  = 0.040), and thalamus ( t (21)  = −2.395, P  = 0.026) were significantly higher in CRPS patients than in healthy controls. Those of globus pallidus ( t (21)  = −2.045, P  = 0.054) tended to be higher in CRPS patients than in healthy controls. In patients with CRPS, there was a positive correlation between the DVR of [ 11 C]-( R )-PK11195 in the caudate nucleus and the pain score, the visual analog scale ( r  = 0.661, P  = 0.026, R 2  = 0.408) and affective subscales of McGill Pain Questionnaire ( r  = 0.604, P  = 0.049, R 2  = 0.364). We demonstrated that neuroinflammation of CRPS patients in basal ganglia. Our results suggest that microglial pathology can be an important pathophysiology of CRPS. Association between the level of caudate nucleus and pain severity indicated that neuroinflammation in this region might play a key role. These results may be essential for developing effective medical treatments.